"Wi, se kretyènn mwen ye" (Yes I am Christian): Methodological Falsehood in Fieldwork - Mézié, Nadège (Fieldwork in religion, 2010)
During a field study of a year and a half in the Haitian mountains, I was forced to re-evaluate my research strategy, and consequently the object of my study, after a setback that denied me access to the American evangelical mission, which I had hoped to study from within. This failure to integrate as a non-Protestant researcher, led me to adopt a methodological falsehood to allow me to penetrate the Haitian evangelical mission. The researcher who chooses methodological falsehood has to fashion a passing and superficial redefinition of her appearance, beliefs and practices, and live her new religious identity according to the prevalent beliefs and norms. This paper will focus on the fieldworker's daily performance in her role of "Christian woman," and the strategies put in place to respond to the prescriptive criteria of the role being played.